Overcoming Teacher Burnout to Improve Performance Through Spiritual Approach Services - Fathor Rozi; Shahzadi Hina; Oyeronke Christiana Paramole (Business and Applied Management Journal, 2025)
This study aims to analyze the approaches in community building, positive habits in educational institutions, and support services and stakeholders in two educational institutions with a comparative concept in dealing with teacher burnout. The focus of this study is to explore how both institutions implement positive habits and stakeholder engagement in an effort to improve the quality of education. This study uses a qualitative approach with a case study method, which includes observation, documentation, and in-depth interviews with key stakeholders in both institutions. The findings indicate that community and positive habits are built through a profoundly spiritual approach, while in the second institution, the main focus is on collaboration between stakeholders and the development of positive habits in the context of modern education. Both institutions show that adequate stakeholder support, such as teacher training and parent involvement, plays an important role in creating a supportive educational environment. The contribution of this study is to provide new insights into understanding the influence of community, positive habits, and the role of stakeholders in improving the quality of education and to suggest an integration between spiritual and modern approaches to achieve more holistic educational success.